Shot through the book - Gates, Eva, 1951- (Gates, Eva, 1951- Lighthouse library mystery., 2025)
"Bestselling author Todd Harrison is murdered on the deck of librarian Lucy McNeil's Outer Banks beach house; caught between an intrusive fan club mourning Todd, squabbling authors, and a politically ruthless widow, Lucy must roll up her sleeves and catch the killer before the chapter closes on justice"--